The Development of Math-Integrated Light and Optical Instruments Teaching Materials Using the Problem-Based Learning Model - Yulia Rahmi; Yanti Fitria (International Journal of Educational Dynamics, 2019)
This study aimed to develop math-integrated light and optical instruments teaching materials using the problem-based learning model that are valid, practical, and effective. This research was developed using a 4D model consisting of stages of defining, designing, developing, and distributing. Teaching materials and learning devices used were validated by experts in terms of education, language and graphics. The subjects of this study were the first semester students of the elementary school teacher study program (PGSD) in a teacher training institution (LPTK). The results showed that the results of the validation of RPS, SAP and teaching materials were on average 91%, 91%, and 83%, respectively. The practicality test results in the trial phase of the first semester students at the LPTK in Region A showed that the percentages of the SAP implementation, responses from lecturers, and responses from students were, on average, 78%, 79%, and 83%, respectively. The effectiveness test was done by viewing the students’ activities in the learning process whose the value was 70%, while the results of their pre-test and post-test were 63.9 and 79.6, respectively, and n-gain was 0.4. The dissemination stage was implemented on the first semester students of the LPTK in Region B. The percentages of the SAP implementation, responses from lecturers, and responses from students were, on average, 83%, 83%, and 77%, respectively, while the achievement of the students in their pre-test and post-test were 64.5 and 81.2, respectively, with n-gain of 0.5. Thus, it can be concluded that the development of math-integrated light and optical instruments teaching materials using the problem-based learning model in this development research was in the criteria of valid, practical, and effective.